Cooling pathways for deep Australian longwall coal mines of the future - Belle, B.; Biffi, M. (International journal of mining science and technology, 2018)
Cooling of coal mines in the Bowen Basin, characterized by steep geothermal gradient, is presently achieved mostly through rental surface bulk air cooling in summer months. This paper argues that future mines will be required to focus their cooling resources more intensively to manage a challenging thermal environment where virgin coal temperatures over 50 °C at a depth of 500 m are expected. Currently, mine cooling systems are employed to maintain the wet bulb temperatures (WBT) to below 27 °C at which point the risks of heat stroke or other heat related issues are manageable. The capacities of these systems are in the range of 6–10 MW refrigeration power. The relationship between high working temperature environment and injury frequency rates is well established. Therefore, provision of appropriate cooling strategies and understanding their optimum performance and suitability are important to Australian coal mines of the future. This paper evaluates the underground temperature profiles of deep, gassy coal mines with propensity for spontaneous combustion and proposes the long term cooling pathways to effectively manage the thermal hazards. Thermodynamic modeling is performed on a longwall face and includes air leakage effects from goaf streams at various locations along the longwall face. The strategy summarizes the application of underground bulk air cooling, chilled water sprays on the shearer and the resulting temperature profiles. Considering the new mining projects planned for the Bowen Basin region, a review of implementable cooling strategies such as mid-gate mobile bulk air coolers (BACs), spot coolers, underground bulk air cooling and the use of chilled water to enhance the positional efficiency of cooling plants, are discussed in this paper. Finally, the comparison of ‘rental’ versus ‘ownership’ of cooling plants is analysed as part of long-term cooling strategies.